Assessment of food safety awareness and hygiene practices among food handlers in Almaty, Kazakhstan - Altyn Kulpiisova; Fatima Dikhanbayeva; Alexandra Tegza; Ivan Tegza; Sholpan Abzhanova; Zamzagul Moldakhmetova; Raushangul Uazhanova; Kuantar Alikhanov; Yerkin Yerzhigitov; Gulnara Shambulova; Gulnara Baikadamova; Gulnur Admanova; et al. (BMC Public Health)
Abstract The current study aimed to evaluate the association between demographic characteristics such as age, gender, education, occupation, employment duration and the food safety knowledge, attitudes, and practices (KAP) among food handlers. The research was based on a cross-sectional study using a questionnaire administered through face-to-face interviews with food handlers employed in small-scale food establishments in Almaty, Kazakhstan. The questionnaire was adapted from previous validated studies and WHO/FAO guidelines. All practices reported in the study were self-reported by the participants. From May to October 2021, 140 small-scale restaurants, cafeterias and eateries were visited. The data collected from 358 food handlers were subjected to statistical analysis using Spearman Correlation and Chi-Square tests. The outcomes of our study demonstrated that a significant proportion of food handlers exhibited positive attitudes toward food safety and adhered to sound food safety practices, however they possessed insufficient knowledge of food safety. Demographic characteristics such as education level, occupation, and work experience in the food service industry were significantly (p < 0.05) associated with food safety KAP.